Hearing loss cases - Syed Mehaboob; HS, Satyan; MG, Subramanyam (Journal of All India Institute of Speech and Hearing)
It has been estimated that 5 percent of our population are suffering from speech and hearing problems (Palmer M. F. 1963). Several other studies have also been reported on the prevalence of hearing loss. (Kapur Y. P. 1967-16.30 per cent, Gupta O. P. 1965-35.40 per cent, Bhatia and Mishra 1961—28 per cent and 30 per cent, Jain S. N. 1967—37 per cent, Kameswaran S. 1967—17 per cent, Nikam S. 1971—3.90 per cent of school going children, Viswanath N. S. et al., 1971—22.80 per cent of rural school going children.) Considering the high incidence cited above, the prevalence of 5 percent as reported by Palmer M. F. (1963) is an underestimation.